Perbandingan Efisiensi Bahan Bakar Pada Kendaraan Low MPV Dengan Metode Copras - Setiawan, Santoso; Marlinda , Linda (Infotek: Jurnal Informatika dan Teknologi, 2024)
Low multi-purpose vehicles have become a popular choice in the automotive market due to their combination of ample space and improved fuel efficiency. In the context of increasing environmental awareness and ever-increasing fuel costs, this study aims to compare the fuel efficiency of various low multi-purpose vehicles using the Complex Proportional Assessment (COPRAS) method. The Copras method, as a multi-criteria decision analysis tool, is used to evaluate vehicle alternatives based on a number of predefined criteria. In this study, the main criteria considered include engine efficiency, aerodynamics, vehicle weight, and fuel technology used. The identification of these criteria is important as fuel efficiency is influenced by various complex technical factors. Relevant data was collected for the low multi-purpose vehicles to be evaluated. Once the data was collected, a Copras analysis was conducted to determine the relative ranking of each vehicle based on its fuel efficiency. This method allowed the researcher to identify vehicles that stood out in terms of fuel efficiency. The results of this study are expected to provide valuable insights for both consumers and vehicle manufacturers. Consumers can use this information to make smarter decisions when choosing a vehicle that suits their needs, taking into account the important aspect of fuel efficiency. On the other hand, manufacturers can use these findings to develop more fuel-efficient vehicles, as well as to strengthen their position in an increasingly competitive market. In addition, this study also has significant implications in an environmental context. By choosing more fuel-efficient vehicles, consumers can contribute to the reduction of greenhouse gas emissions and reduce other negative impacts on the environment. As such, this research not only provides economic benefits but also supports efforts to maintain environmental sustainability